ANALISIS PENGARUH CITRA MEREK, PROMOSI, KEPERCAYAAN KONSUMEN, DAN KUALITAS LAYANAN TERHADAP KEPUTUSAN PEMBELIAN MELALUI APLIKASI SHOPEE FOOD (KASUS PADA PENGGUNA LAYANAN SHOPEE FOOD YANG BERDOMISILI DI KOTA SEMARANG) - Rafif Zharif Primaputra; Budi Sudaryanto (Diponegoro Journal of Management, 2023)
ABSTRACT This research is motivated by the condition of competition in the food delivery service application business from time to time which is getting tighter, so companies must create new marketing strategies to maintain and gain a higher market share. This study tries to find out the factors that influence customer purchasing decisions for the food and beverage delivery service application Shopee Food in Semarang City. The purpose of this study was to analyze the effect of each variable, purchase decision (X1), promotion (X2), consumer trust (X3), and service quality (X4) on purchasing decisions (Y). In this study, data were collected using a questionnaire method on 100 respondents using a purposive sampling method to determine respondents' responses to each variable. Then performed an analysis of the data obtained in the form of quantitative analysis and qualitative analysis. Quantitative analysis includes validity and reliability tests, classic assumption tests, hypothesis testing via the F test and t test as well as analysis of the coefficient of determination (R2). The data analysis technique used is multiple linear regression analysis which serves to prove the research hypothesis. The results of the analysis find that the four factors of brand image, promotion, consumer trust, and service quality have a positive and significant influence on purchasing decisions. Testing the hypothesis using the t test shows that the four independent variables studied are proven to significantly influence the dependent variable in purchasing decisions. Then through the F test it can be seen that the variables brand image, promotion, consumer trust, and service quality have a significant effect on purchasing decisions together. Adjusted R square of 0.831 indicates that 82.4 percent of the variation in purchasing decisions can be explained by the four independent variables used in the regression equation. While the remaining 17.6 percent is explained by other variables outside the four variables used in this study